The mediating effect of life satisfaction between daily living abilities and depressive symptoms in the Chinese older people: evidence from CHARLS 2020 - Liao, Mingsheng; Zhang, Xuesi; Xie, Zhiquan; Li, Limei; Zou, Liqin (Frontiers in Public Health, 2024)
Background: Depressive symptoms represent a significant public health challenge, impacting the mental well-being of older adults. Despite this, the understanding of how activities of daily living (ADL) abilities correlate with life satisfaction and depressive symptoms among older Chinese adults remains limited.Aims: This study aims to investigate the relationship between ADL and depressive symptoms in elderly Chinese individuals, with a specific focus on examining the mediating role of life satisfaction within this context.The study utilized data from the China Health and Retirement Longitudinal Study (CHARLS) collected in 2020. A cohort of 8,343 individuals aged 60 years and above was included. The analysis was conducted using STATA 17.0 and SPSS 26.0, employing descriptive statistics, chi-square tests, Pearson correlations, and mediation analysis using the percentile Bootstrap method with 5,000 resamples to explore the interrelations among ADL, life satisfaction, and depressive symptoms.Results: ADL is positively correlated with life satisfaction (r=0.129, P<0.01) and negatively correlated with depressive symptoms (r=-0.313, P<0.01). Additionally, life satisfaction and depressive symptoms are negatively correlated with each other (r=-0.360, P<0.01). In the model of the mediating effect, ADL directly, significantly and negatively predicts depressive symptoms in the Chinese elderly (β=-0.193, t=-17.827, P<0.001). After incorporating life satisfaction into the regression equation, the direct predictive effect of ADL on depressive symptoms remains significant (β=-0.177, t=-17.099, P<0.001); furthermore, ADL has a significant positive predictive effect on life satisfaction (β=0.007, t=4.959, P<0.001) and life satisfaction significantly negatively predicts depressive symptoms (β=-2.235, t=-27.799, P<0.001). Furthermore, the direct effect of ADL on depressive symptoms (-0.177) and its mediating effect (-0.016) account for 91.71% and 8.29% of the total effect (-0.193), 3 respectively.ADL is inversely associated with the risk of depressive symptoms among elderly Chinese individuals, with life satisfaction serving as a significant mediator in this relationship. Interventions aimed at improving life satisfaction in elderly individuals with ADL impairments may effectively reduce or prevent the onset of depressive symptoms.